2022
DOI: 10.1016/j.biopsych.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Childhood and Adolescent Anxiety and Risk for Psychosis: A Longitudinal Birth Cohort Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…First, other potential contributing factors, such as depression, cognition, obstetric complications, viral infections, smoking or body mass index, which could have some effect on the results were left unexplored. For this study, we decided to control only for socio‐demographic factors and early life family adversities and not to over‐control for variables, consistent with our previous research using this cohort (Morales‐Muñoz et al., 2020 ; Morales‐Muñoz, Palmer, Marwaha, Mallikarjun, & Upthegrove, 2022 ); however, further relevant confounders should be also explored in future studies. Second, probable ADHD at 10 years was coded by collecting information from parents, and thus parental perceptions and/or assumptions could bias this assessment.…”
Section: Discussionmentioning
confidence: 99%
“…First, other potential contributing factors, such as depression, cognition, obstetric complications, viral infections, smoking or body mass index, which could have some effect on the results were left unexplored. For this study, we decided to control only for socio‐demographic factors and early life family adversities and not to over‐control for variables, consistent with our previous research using this cohort (Morales‐Muñoz et al., 2020 ; Morales‐Muñoz, Palmer, Marwaha, Mallikarjun, & Upthegrove, 2022 ); however, further relevant confounders should be also explored in future studies. Second, probable ADHD at 10 years was coded by collecting information from parents, and thus parental perceptions and/or assumptions could bias this assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might suggest that only clinically relevant anxiety symptoms might be associated with the occurrence of PLEs. Of note, causality cannot be established in our study; however, a longitudinal study of children and adolescents demonstrated that persistent high levels of anxiety predict the development of PLEs and psychotic disorders at the age of 24 years [44]. Similarly, cross-sectional studies, based on clinical samples, revealed the association between anxiety disorders and PLEs [45, 46].…”
Section: Discussionmentioning
confidence: 66%
“…The findings of our current study are congruent with a recent study of ours using ALSPAC data where we found that IL-6 level, but not CRP level (both at 9 years), partially mediated the associations between sleep problems in childhood and ADHD diagnosis at 10 years. Another recent study from our group also using ALSPAC data found that CRP level at 9 and 15 years, but not IL-6 level at 9 years, partially mediated the associations between persistent anxiety across childhood and psychosis at 24 years. Based on this limited evidence, we could hypothesize that different physiological actions associate with each of these inflammatory markers ; thus, IL-6 level may be more sensitive to sleep problems, although anxiety may have a greater association with CRP levels, in the pathway to psychosis.…”
Section: Discussionmentioning
confidence: 99%